Effect of a silicon-based sealing agent (GapSeal) on the reverse torque value of the abutment–implant screw - Talayeh Katebi; Soolmaz Heidari; Shima Aalaei (Journal of Dental Materials and Techniques, 2024)
Objective: One major cause of dental implant failure is screw loosening. Silicone sealants have been introduced to reduce the gap between abutments and implants, potentially reducing screw loosening. This study aimed to investigate the effect of using a sealing agent on the reverse torque value (RTV) of abutment–implant screws.Methods: Sixteen implants were divided into experimental and control groups (N=8). GapSeal gel was injected into the fixture's intaglio cavity in the experimental group, while the control group received no injection. The abutments were tightened to the fixtures with a torque of 30 N.cm for all samples. Additionally, full-metal crowns were cemented onto each abutment. The implants underwent axial cyclic loading, with 500,000 cycles at a force of 75 N and a frequency of 2 Hz applied along the longitudinal axis of each sample. The detorque value was measured for all samples using a digital torque meter. Data were analyzed using an independent samples t-test, with significance set at P < 0.05.Results: The mean reversed torque of the study group (18.50 ± 0.71 N.cm) was significantly higher than the control group (11.375 ± 0.43 N.cm; P < 0.001). The difference between the initial tightening torque value (TTV) and RTV (11.50 ± 0.56 N.cm) in the study group was significantly lower than that in the control group (18.62 ± 034 N.cm; P=0.001).Conclusions: The GapSeal gel reduced the torque loss value of the abutment–implant screw and may be recommended in clinical settings to reduce the risk of screw loosening.